Immunohistochemical Detection of Neural Stem Cells and Glioblastoma Stem Cells in the Subventricular Zone of Glioblastoma Patients. (May 2021) - Hira, Vashendriya V.V.; Molenaar, Remco J.; Breznik, Barbara; Lah, Tamara; Aronica, Eleonora; Van Noorden, Cornelis J.F.
Glioblastoma usually recurs after therapy consisting of surgery, radiotherapy, and chemotherapy. Recurrence is at least partly caused by glioblastoma stem cells (GSCs) that are maintained in intratumoral hypoxic peri-arteriolar microenvironments, or niches, in a slowly dividing state that renders GSCs resistant to radiotherapy and chemotherapy. Because the subventricular zone (SVZ) is a major niche for neural stem cells (NSCs) in the brain, we investigated whether GSCs are present in the SVZ at distance from the glioblastoma tumor. We characterized the SVZ of brains of seven glioblastoma patients using fluorescence immunohistochemistry and image analysis. NSCs were identified by CD133 and SOX2 but not CD9 expression, whereas GSCs were positive for all three biomarkers. NSCs were present in all seven samples and GSCs in six out of seven samples. The SVZ in all samples were hypoxic and expressed the same relevant chemokines and their receptors as GSC niches in glioblastoma tumors: stromal-derived factor-1α (SDF-1α), C-X-C receptor type 4 (CXCR4), osteopontin, and CD44. In conclusion, in glioblastoma patients, GSCs are present at distance from the glioblastoma tumor in the SVZ. These findings suggest that GSCs in the SVZ niche are protected against radiotherapy and chemotherapy and protected against surgical resection due to their distant localization and thus may contribute to tumor recurrence after therapy.